PENGARUH PENERAPAN MODEL PEMBELAJARAN INDEXS CARD MATCH UNTUK MENINGKATKAN MOTIVASI BELAJAR PPKn SISWA KELAS VII SMPN 1 SIBOLANGIT - Henny Wahyuni; Sri Erlinda; Haryono Haryono (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstrak: This research is motivated by the low motivation to learn PPKn class VII students of Sibolangit 1 Junior High School. The formulation of the problem in this study is: "What is the Effect of the Application of the Indext Card Learning Model Match on the Learning Motivation of Students in Class VII of SMPN 1 Sibolangit" ?. This study aims to determine the effect of the use of the Indext Card Match learning model on PPKn learning motivation for grade VII students of Sibolangit 1 Junior High School. This type of research is experimental research. The study was conducted at Sibolangit 1 Junior High School. Samples from this study were students of class VII1 as an experimental class and students in class VII3 as a control class, this sample was determined randomly after homogeneity testing in all populations. The experimental class is a class that is given a treatment using the Index Card Match learning model, while the control class is the class that is treated using the conventional Conventional method. Based on the analysis of the difference test "t" of the two classes shows t count> t table (38.1> 20.00), which means there is a significant influence between using the card match index learning model with conventional methods. Thus the use of the card match index learning model has a positive and significant influence on students' learning motivation in the class VII PPKn subjects at Sibolangit Middle School 1. Observation activities of teachers who were taught using the card match index model at the first meeting were 93.7% with the "perfect" category and at the second meeting increased to 96.1% with the "perfect" category to determine the level of activity of the experimental teacher from the first meeting and the second meeting was averaged at 97.30% with the category "very perfect". Thus the hypothesis that reads there is the influence of the use of the Indext Card Match learning model on PPKn learning motivation for grade VII students of Sibolangit 1 Junior High School, can be accepted.Key words: Card Match Index, Learning Motivation